The coagulation consult : a case-based guide - Bartholomew, John; Lichtin, Alan (Springer New York, 2014)
There have been many changes in the field of coagulation during the past decade. New concepts of epidemiology of risk factors for thrombosis now help clinicians predict who is more likely to form clots after surgery, or after being placed on oral contraceptives. New anticoagulants have the potential to redefine how patients with atrial fibrillation and venous thrombosis are managed. There are new forms of recombinant clotting factors which have changed our approach to hypofibrinogenemia and von Willebrand's disease. Newer antiplatelet agents are available and their use in patients receiving cardiac stents has mushroomed. The management of thrombosis in the setting of pregnancy has changed over the past decade, as well as the way clinicians approach women with multiple miscarriages. An entire new class of compounds, the thrombopoietins, are available to treat individuals with immune thrombocytopenic purpura (ITP). The Coagulation Consult covers major topics of interest to hematologists who are asked to consult on individuals with coagulation related diseases, and encompasses the field's most recent developments. This "case-directed" book describes state-of-the-art approaches to patients with bleeding and clotting disorders, as well as laboratory tests for coagulation. Chapters include different vignettes, focus on typical clinical consult questions, and lay out specific types of treatment. Practicing clinicians being confronted with a coagulation consult, students, residents, fellows and attending physicians will find this unique text an invaluable resource for some of the newer areas of coagulation science, therapy and pharmacology.